Tingkat Kepuasan Petani pada Kinerja Kelembagaan Agribisnis Kedelai di Jawa Tengah - Ratna Satriani; Rifda Naufalin; Akhmad Rizqul Karim; Eni Hari Widowati; Alfina Handayani; Rifki Andi Novia (Jurnal Ilmu Pertanian Indonesia, 2023)
The soybean agribusiness institutions have important roles to support the increased soybean production in Central Java. The purpose of this study was to analyze the levels of performance and importance of farmers in the institutional performance of soybean agribusiness in Central Java. This research uses descriptive analytical method, with the technical implementation of research using survey methods. This research was conducted on September - December 2022 with a sampling technique using a purposive sampling on 110 respondent farmers. Data analysis carried out in this research is Importance and Performance Analysis (IPA). IPA is used to compare the level of importance of soybean farmers with their levels of performances. Before being analyzed using IPA, each attribute was tested for validity and reliability, and from the test results it was found that each attribute was declared valid and reliable. The results of the analysis show that one of the attributes that is included in quadrant I and needs to be a priority for improvement is the need to determine the Harga Pokok Produksi (HPP) for soybeans by the government and the need to increase the subsidized fertilizer program. Attributes that fall into quadrant II and whose performances must be maintained include the existence of collector traders, the existence of a soybean seed assistance program, and the availability of quality soybean seeds. Attributes that are included in quadrant III and are the second priority for repairing and improvement are the need for storage granaries, partnerships with companies, and the easy access to financing services. Meanwhile, the attributes that enter quadrant IV and can be ignored are the availabilities of water, labor, and farming infrastructure. Keywords: importance and performance analysis, importance farmers, performance farmers, soybeans